Censorship detected in EG (Egypt) - Voidly (2025)
CRITICAL severity censorship detected in Egypt. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: EG-2025-0002
Keywords: censorship; EG; censorship; critical